Conservative management of unicystic ameloblastoma in a young child: Report of two cases - Ritesh Kalaskar; Ashok S Unawane; Ashita R Kalaskar; Prashant Pandilwar (Wolters Kluwer Medknow Publications, 2011)
Unicystic ameloblastoma is a rare, benign, locally invasive odontogenic neoplasm of young age that show clinical, radiographic, or gross features of an odontogenic cyst, but histologically shows typical ameloblastomatous epithelium lining part of the cyst cavity, with or without luminal and/or mural tumor growth. The article presents atypical cases of a large, asymptomatic unicystic ameloblastoma of posterior maxilla and mandibular molar-ramus regions which were treated by surgical enucleation and application of Carnoy's solution for 3 min. The article also describes the importance and complexity of differential diagnosis of an odontogenic lesion sharing common clinical and radiographical features.